Internet difussion in Muslim community: a case study among sub-urban Malays in Malaysia - Ali Salman; Mohd. Safar Hasim (Fakulti Sains Sosial dan Kemanusiaan, 2012)
This paper presents a study on the adoption and usage of internet by Malay Muslims living in a sub-urban area as an attempt to answer the following questions:what is the situation of ICT implementation in Malaysia, what is the nature and purpose of usage of the internet by the Malay Muslims that warrant them a place as active users of ICT. This study used survey research method to obtain data from the malay population in Kota Bharu. This study used purposive sampling focusing on the respondents who are already using the internet.The Data were analysed using SPSS 12.0 and the analysis was descriptive. It is found that newspaper has been the main source of information. This is followed by internet,. Email is the main purpose of using the internet, and this is followed closely by reading newspaper and searching for information . Job related usage is the third main purpose of usage , and about half use the internet for social communication. This study has lent support to the diffusion of innovation theory, from the study it is obvious the Malays are ready and quick in adopting new technology in this case ICT into their lifestyle.